FENOMENA PENGELOLAAN ATRAKSI WISATA SWAFOTO DAN IMPLIKASINYA BAGI MASYARAKAT DI DESA WANAGIRI KECAMATAN SUKASADA KABUPATEN BULELENG - I Gede Ngurah Wirayuda Arsana; I Nyoman Sunarta; I Nyoman Sukma Arida (JURNAL MASTER PARIWISATA, 2019)
The increase in number of tourists dominated by millenials that always wants to get attention on Instagram (instagrammable) or other social media, such as facebook, whatsapp, line, and twitter giving opportunities to community of Wanagiri Village for developing selfie tourism. Along with their creativity, community of Wanagiri Village carried out selfie tourism around Nature Tourism Park of Lake Buyan and Tamblingan, which increased disharmony between local people (in this case represented by desa adat) with local government. This research was conducted based on qualitative research with descriptive model, which the purposes are: 1) Knowing the development of selfie tourism in Wanagiri Village; 2) Examining the implementation of policies for selfie tourism in Wanagiri Village; 3) Knowing the implications of selfie tourism for local people in Wanagiri Village. The results showed three main things. First, selfie tourism in Wanagiri Village creates relation pattern between the desa adat Wanagiri, Bali Natural Resources Conservation Center, Buleleng Regency Tourism Office, and the investors. The relation pattern forms synergy that occurs between all of them through the beliefs and all parties to regulation, as happened in Balinese concept "Sagilik Saguluk Salunglung Sabayantaka". Second, there are job diversification. Last, public awareness of nature conservation can be maintained. Keywords: Selfie tourism, Wanagiri Village, Development policy